Death anxiety in patients with primary brain tumor: Measurement, prevalence, and determinants. Issue 6 (December 2021) - Loughan, Ashlee R.; Husain, Mariya; Ravyts, Scott G.; Willis, Kelcie D.; Braun, Sarah Ellen; Brechbiel, Julia K.; Aslanzadeh, Farah J.; Rodin, Gary; Svikis, Dace S.; Thacker, Leroy
Abstract: Objective: This study investigated death anxiety in patients with primary brain tumor (PBT). We examined the psychometric properties of two validated death anxiety measures and determined the prevalence and possible determinants of death anxiety in this often-overlooked population. Methods: Two cross-sectional studies in neuro-oncology were conducted. In Study 1, 81 patients with PBT completed psychological questionnaires, including the Templer Death Anxiety Scale (DAS). In Study 2, 109 patients with PBT completed similar questionnaires, including the Death and Dying Distress Scale (DADDS). Medical and disease-specific variables were collected across participants in both studies. Psychometric properties, including construct validity, internal consistency, and concurrent validity, were investigated. Levels of distress were analyzed using frequencies, and determinants of death anxiety were identified using logistic regression. Results: The DADDS was more psychometrically sound than the DAS in patients with PBT. Overall, 66% of PBT patients endorsed at least one symptom of distress about death and dying, with 48% experiencing moderate-severe death anxiety. Generalized anxiety symptoms and the fear of recurrence significantly predicted death anxiety. Significance of results: The DADDS is a more appropriate instrument than the DAS to assess death anxiety in neuro-oncology. The proportion of patients with PBT who experience death anxiety appears to be higher than in other advanced cancer populations. Death anxiety is a highly distressing symptom, especially when coupled with generalized anxiety and fears of disease progression, which appears to be the case in patients with PBT. Our findings call for routine monitoring and the treatment of death anxiety in neuro-oncology.